Flowering plants of Sarkuwa VDC, Baglung, Western Nepal - Bhagat, Indramani; Subedi, Bimala (Nepalese Journal of Biosciences, 2017)
The study was conducted in Sarkuwa VDC of Baglung district, Western Nepal to explore and document the flowering plants. Altogether 127 species of plants belonging to108 genera and 53 families were collected. Dominant families of the study area are Moraceae with 11 species, Asteraceae with 9 species, Fabaceae and Euphorbiaceae with 8 species, Lamiaceae and Verbenaceae with 5 species and Anacardiceae, Meliaceae, Poaceae with 4 species. Among the 127 species, trees are dominant in species composition attaining 39.37 of the whole floristic value, shrub with 27.55%, herb with 25.19%, and climber with 5.15%, under shrub with 1.57% and finally parasite by attaining 0.78%.